Integrated Approach for Shoreline Management Plan for Coastline of Sarawak - Mohammad Razi, Mohd Adib; Mahamud, Mahran; Hashim, Siti Aishah; Mokhtar, Arman (Penerbit UTHM, 2020)
The Integrated Shoreline Management Plan (ISMP) has been instituted by DID as Malaysia's response in support of Agenda 21 of the Rio Declaration, and as a pragmatic mechanism to enhance coastal zone management and development planning in the country for the long term benefit of the nation. ISMP is considered as a subset of Integrated Coastal Zone Management Plans (ICZM) with emphases and details on developments along the shoreline. ICZM focuses on regional and international scale of the coastal zone with broader management strategies. This chapter provides the shoreline evolution study that has been carried out for 336 km length of coastline from the Kuching Division border to the Betong Division border. The obtained erosion rates then are compared against the erosion rates published between NCES 1985 and NCES 2015.